Effect of Mix Design Variables on Thermal Cracking Performance Parameters of Asphalt Mixtures. Issue 28 (December 2018) - Oshone, Mirkat; Ghosh, Debaroti; Dave, Eshan V.; Daniel, Jo Sias; Voels, Joseph M.; Dai, Shongtao
To address asphalt pavement thermal cracking, researchers have developed performance-based evaluation tools for asphalt mixtures. A minimum fracture energy obtained from a disc-shaped compact tension test and Black space parameters determined by the stiffness and relaxation properties of asphalt mixtures are two such methods to ensure good thermal cracking resistance. Mix specifiers and producers strive to meet the requirements set by these performance-based criteria by adjusting their mix designs. However, there is a lack of information and consensus on the effect of mix design variables (such as binder grade and mix volumetrics) on thermal cracking performance of mixtures as it relates to fracture energy and Black space location. This study strives to fill this gap by quantifying the effect of: (1) recycled asphalt content, (2) effective binder content, (3) air voids, (4) asphalt film thickness, (5) voids in mineral aggregates, and (6) PG low and high temperature grades on thermal cracking resistance. A large dataset, 90 mixtures from the Minnesota Department of Transportation and 81 mixtures from University of New Hampshire database, was used for the study. The results indicate a strong correlation between binder related properties (binder content, asphalt film thickness, PG spread) and fracture energy. The correlation coefficients obtained from this study for PG spread, effective binder content, and air void can be confidently employed to achieve targeted fracture energy thresholds. The same can be achieved for the Glower-Rowe parameter at 15ºC by employing the correlation coefficients obtained for PG low temperature, virgin asphalt content, and voids in the mineral aggregate.